2010
DOI: 10.1007/s11606-009-1224-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Wars on Smoking Among Veterans

Abstract: A lthough smoking rates in the US declined by 50% between 1965 and 2005, about 21% of adults are current smokers. 1,2 The prevalence of smoking is estimated to be up to 40% higher in veterans than in the general population. 3,4 The total burden of Veterans Affairs (VA) health-care costs associated with smoking range from 8% to 24%. 5 While the VA has increased its efforts to fight the "war" on smoking, 6 actual wars in Iraq and Afghanistan are producing veterans who are smoking at alarming rates. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…The rates of elevated BMI in our sample were higher than those reported in other groups of Veterans [22][23]. The prevalence of smoking was similar to that reported among other OIF/OEF/OND Veterans [24][25][26].…”
Section: Discussionsupporting
confidence: 79%
“…The rates of elevated BMI in our sample were higher than those reported in other groups of Veterans [22][23]. The prevalence of smoking was similar to that reported among other OIF/OEF/OND Veterans [24][25][26].…”
Section: Discussionsupporting
confidence: 79%
“…The US military Millennium Cohort Study, a 21-year prospective study, has demonstrated that operational deployment is associated with an increased risk of both smoking initiation in previous never-smokers and a resumption of smoking in ex-smokers, and that the risk is further increased with exposure to combat [ 33 ]. There is good evidence that US troops returning from Afghanistan are smoking heavily [ 34 ]. A small study in US troops serving in Afghanistan in 2011 found that 62 % of deployed personnel smoked and that 29 % had increased their tobacco usage whilst deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, OEF/OIF war initiatives are producing veterans who use tobacco at alarming rates, with smoking initiation rates at 7% (Bastian & Sherman, 2010;Beckham et al, 2008). Once tobacco use is initiated in the military there is a pattern of increased lifelong tobacco use (Beckham et al, 2008).…”
Section: Organizational Barriers To Smoking Cessationmentioning
confidence: 99%